Perfusion Quantification in Contrast-Enhanced Ultrasound (CEUS) – Ready for Research Projects and Routine Clinical Use - Tranquart, F.; Mercier, L.; Frinking, P.; Gaud, E.; Arditi, M. (Ultraschall in der Medizin - European Journal of Ultrasound, 2012)
With contrast-enhanced ultrasound (CEUS) now established as a valuable imaging modality for many applications, a more specific demand has recently emerged for quantifying perfusion and using measured parameters as objective indicators for various disease states. However, CEUS perfusion quantification remains challenging and is not well integrated in daily clinical practice. The development of VueBox™ alleviates existing limitations and enables quantification in a standardized way. VueBox™ operates as an off-line software application, after dynamic contrast-enhanced ultrasound (DCE-US) is performed. It enables linearization of DICOM clips, assessment of perfusion using patented curve-fitting models, and generation of parametric images by synthesizing perfusion information at the pixel level using color coding. VueBox™ is compatible with most of the available ultrasound platforms (nonlinear contrast-enabled), has the ability to process both bolus and disruption-replenishment kinetics loops, allows analysis results and their context to be saved, and generates analysis reports automatically. Specific features have been added to VueBox™, such as fully automatic in-plane motion compensation and an easy-to-use clip editor. Processing time has been reduced as a result of parallel programming optimized for multi-core processors. A long list of perfusion parameters is available for each of the two administration modes to address all possible demands currently reported in the literature for diagnosis or treatment monitoring. In conclusion, VueBox™ is a valid and robust quantification tool to be used for standardizing perfusion quantification and to improve the reproducibility of results across centers.
Keywords: dynamic contrast-enhanced ultrasound; perfusion; quantification; treatment monitoring; parametric images.